2019
DOI: 10.3892/mmr.2019.9921
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pathogenic mutation in a Chinese pedigree with polycystic kidney disease

Abstract: Polycystic kidney disease (PKD) is a life-threatening inherited disease with a morbidity of 1:500–1,000 worldwide. Numerous progressively enlarging cysts are observed in the bilateral kidneys of patients with PKD, inducing structural damage and loss of kidney function. The present study analyzed one family with PKD. Whole exome sequencing of the proband was performed to detect the pathogenic gene present in the family. Candidate gene segments for lineal consanguinity in the family were amplified by nest polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…To date, more than 2,000 mutations in PKD1 and about 400 mutations in PKD2 have been identified in people with ADPKD ( Dong et al, 2019 ). Most mutations in PKD1 result in expression of the abnormally small, non-functional PC1 protein, which likely interrupts intracellular and ciliary signaling pathways, resulting in atypical cell growth and proliferation ( Hopp et al, 2012 ; Cai et al, 2014 ; Cebotaru et al, 2014 ; Kurbegovic et al, 2014 ).…”
Section: Current Knowledge About the Structure And Function Of Pc1 Pc2 And Fpcmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, more than 2,000 mutations in PKD1 and about 400 mutations in PKD2 have been identified in people with ADPKD ( Dong et al, 2019 ). Most mutations in PKD1 result in expression of the abnormally small, non-functional PC1 protein, which likely interrupts intracellular and ciliary signaling pathways, resulting in atypical cell growth and proliferation ( Hopp et al, 2012 ; Cai et al, 2014 ; Cebotaru et al, 2014 ; Kurbegovic et al, 2014 ).…”
Section: Current Knowledge About the Structure And Function Of Pc1 Pc2 And Fpcmentioning
confidence: 99%
“…ADPKD is usually diagnosed later in life, while ARPKD develops during prenatal development, or in early childhood. ADPKD is mainly associated with mutations in the PKD1 or PKD2 genes encoding the polycystin-1 and -2 proteins (PC1 and PC2), respectively (Dong et al, 2019). The primary cause of ARPKD is mutations in the PKHD1 gene encoding the fibrocystin/polyductin protein (FPC; Burgmaier et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Our data identify PC-1’s CTL domain as an essential component for polycystin activation. Interestingly, the CTL domain is a hotspot for ADPKD-causing mutations ( Dong et al, 2019 ), supporting the critical importance of this domain ( Figure 2—figure supplement 1B ). Although C-type lectins are the most diverse family of mammalian carbohydrate-binding proteins ( Keller and Rademacher, 2020 ), little is known about the function of the CTL motif within PC-1 ( Sandford et al, 1997 ), but it has been reported to bind to carbohydrates in a calcium-dependent manner ( Weston et al, 2001 ).…”
Section: Discussionmentioning
confidence: 58%
“…* indicates 100% conserved amino acid residues. ( B ) Adhesion domains present in NTF 25-853 and the number and location of ADPKD-causing mutations reported to date (18 mutations have been reported for the CTL domain [ Dong et al, 2019 ]). Sequence alignment of the CTL domain from human PC-1 and PC-1L3.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of the variant in affected individuals is significantly increased compared with the prevalence in controls (PS4). Variants are sited in mutational hotspots (Dong et al, 2019), in which pathogenic variants in one or several nearby residues have been observed with greater frequency (PM1). Variants that are absent from gnomAD, 1000 Genome Program and ExAC databases are considered follow a moderate piece of evidence for pathogenicity (PM2).…”
Section: Resultsmentioning
confidence: 99%